Haemostatic effects of latex from Croton sparsiflorus Morang, in vitro, in vivo, in silico approaches. (June 2018) - Kamaraj, M.C.; Mohan Raj, S.; Palani Selvam, D.; Subashchandrabose, S.; Kalaiselvan, A.
Graphical abstract: Highlights: Crud sample extracted from Traditional plant. Molecular structure of the target sample was found. In-vitro and in-vivo blood clotting activity studied. Explained the mechanism of the blood clotting activity. Docking and DFT computational studies were carried out. Abstract: The present investigations are phytochemical screening of Latex aqueous (Laq ) extract of C. sparsiflorus and study its role in homeostasis. It is being traditionally used for fresh cuts to stop bleeding immediately. To know the contents of extract, the quantitative phytochemical analysis were performed it showed the contents such as saponins (15.2%), alkaloids (7.61%), phenols (0.62%), tannins (1.1%), and flavonoids (0.224%). The in vitro and in vivo blood clotting mechanism was observed in Wister albino rats to understand the blood clotting activity. The in vitro cytotoxicity assay was performed by 3T3L1 cell lines evaluated by Laq extract of C. sparsiflorus to determine the toxic effects of the extract. The gas chromatographic and liquid chromatographic mass spectra (GCMS and LCMS) were observed there were three compounds obtained namely, 1) methyl-hexafuranoside, 2) cumarandione, and 3) crotonosine, in addition to that the NMR ( 1 H and 13 C) elemental analysis, FT-IR (4000–400 cm −1 ) and UV–vis (800–200 nm) spectra were also recorded in aqueous solution. The molecular docking studies performed, in which the blood clotting factors have a potential interaction with crotonosine. This in-silico study demonstrates the interactions of active components of C. sparsiflorus with blood clotting factors. Furthermore, since the crotonosine compound has more blood clotting factor the molecular structure was treated with density functional theory calculation (DFT) to understand the optimized geometry, vibrational behaviour and electronic excitation states.